(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2015)
Examination of dust collected from the homes of asthmatic patients showed there were significant numbers of house dust mites (HDM). The allergens generated from HDM are considered to be among the risk factors for asthma development. HDM can be identified in mattresses, carpets, quilts and pillows. HDM are about 0.2 x 0.3 mm in size, so they are only clearly visible under microscopic magnification. Therefore, it is important to develop a trapping kit to capture and stain them. We devised a trapping kit that is comprised of an adhesive pad and a staining agent. The adhesive pad is made of cotton cloth and is coated with glue, which can attract and trap HDM to prevent them from further spreading. The staining agent contains nanogold-coupled monoclone antibodies, which can react with HDM through binding with group 2 allergens on the body surface of HDM. After staining, both Dermatophagoides pteronyssinus (Dp) and Tyrophagus putrescentiae (Tp) become visible to the naked eye.Our study showed that the HDM trapping pad can attract and trap HDM. The staining agent makes them visible so they can be counted. This kit can help us to identify the predominant HDM infestation area in the household environment. By identifying the infestation area, we can reduce HDM exposure and prevent the development of allergic disease.